Manenberg Negotiated: answering questions communities are not asking - Hedley, Phillipa A (School of Architecture, Planning and Geomatics, 2020)
Within the global South, the public realm is often characterised as a territory of intense accessibility and spatial claims, equally enabling and constricting citizens to shape and reshape an inclusive place within the informal city. The contemporary African city has been central to the discourse around the rapidity of urban development and influx, producing a global narrative of the inability of a frail postcolonial metropolis to support this growth. What is emerging, however, is the resulting improvisation of the city’s inhabitants to reimagine their contrasting, everyday environments for the city’s negotiation and daily navigation. Often, the global discourse omits the finer, more nuanced informality of life that the African city’s marginalised users employ in the everyday to innovatively sustain their livelihood.